Analisis Postur Kerja dengan Menggunakan Perbandingan Metode RULA REBA dan OWAS pada Pegawai PT. Surya Segara Safety Marine Paper - Fitra, Nabila Jania; Tranggono, Tranggono (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
PT Surya Segara Safety Marine is a marine equipment trading and maritime security equipment servicing company in Indonesia that has four branches in Balikpapan, Makassar, Banyuwangi, and Bali. In their work, there are workers who have not implemented ergonomic working positions. This research aims to determine the action level value from the comparison scores of the RULA, REBA, and OWAS methods. From the research that has been carried out, it is known from the NBM questionnaire that 77% of workers experience back pain and 70% experience low back pain. Regarding the scoring results, a RULA score of 7 is very high risk, a REBA score of 9 is high risk, and an OWAS score of 2 is moderate risk. Based on the data obtained, the RULA method is most suitable because of the complaints felt by workers in the upper body. So a proposal to improve a table that can rotate and a chair that can be adjusted in height was made, which received a RULA score of 2 out of 7, where this value was better than the initial score before the improvement proposal was given.